9c(3c+5)(4c-11)=0

Simple and best practice solution for 9c(3c+5)(4c-11)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9c(3c+5)(4c-11)=0 equation:


Simplifying
9c(3c + 5)(4c + -11) = 0

Reorder the terms:
9c(5 + 3c)(4c + -11) = 0

Reorder the terms:
9c(5 + 3c)(-11 + 4c) = 0

Multiply (5 + 3c) * (-11 + 4c)
9c(5(-11 + 4c) + 3c * (-11 + 4c)) = 0
9c((-11 * 5 + 4c * 5) + 3c * (-11 + 4c)) = 0
9c((-55 + 20c) + 3c * (-11 + 4c)) = 0
9c(-55 + 20c + (-11 * 3c + 4c * 3c)) = 0
9c(-55 + 20c + (-33c + 12c2)) = 0

Combine like terms: 20c + -33c = -13c
9c(-55 + -13c + 12c2) = 0
(-55 * 9c + -13c * 9c + 12c2 * 9c) = 0
(-495c + -117c2 + 108c3) = 0

Solving
-495c + -117c2 + 108c3 = 0

Solving for variable 'c'.

Factor out the Greatest Common Factor (GCF), '9c'.
9c(-55 + -13c + 12c2) = 0

Factor a trinomial.
9c((-5 + -3c)(11 + -4c)) = 0

Ignore the factor 9.

Subproblem 1

Set the factor 'c' equal to zero and attempt to solve: Simplifying c = 0 Solving c = 0 Move all terms containing c to the left, all other terms to the right. Simplifying c = 0

Subproblem 2

Set the factor '(-5 + -3c)' equal to zero and attempt to solve: Simplifying -5 + -3c = 0 Solving -5 + -3c = 0 Move all terms containing c to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -3c = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -3c = 0 + 5 -3c = 0 + 5 Combine like terms: 0 + 5 = 5 -3c = 5 Divide each side by '-3'. c = -1.666666667 Simplifying c = -1.666666667

Subproblem 3

Set the factor '(11 + -4c)' equal to zero and attempt to solve: Simplifying 11 + -4c = 0 Solving 11 + -4c = 0 Move all terms containing c to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -4c = 0 + -11 Combine like terms: 11 + -11 = 0 0 + -4c = 0 + -11 -4c = 0 + -11 Combine like terms: 0 + -11 = -11 -4c = -11 Divide each side by '-4'. c = 2.75 Simplifying c = 2.75

Solution

c = {0, -1.666666667, 2.75}

See similar equations:

| 73=f(x) | | 6x+15-2x=-25 | | log(x)2=0 | | 4/7(15.5) | | 2h/3-0.25=.33 | | -2(x+3)+5x=4-2x-5 | | 3.6+m=2 | | Logx(0.5x+4)=0 | | F(x)=73 | | -11=61-6f | | w+5w+9= | | 81-4x=121-6x | | 7k-11= | | -8-3d=25 | | 2(x-8)=x+3-12 | | 10n=240 | | 24.25/.75 | | 13(9c-3)=5c-8 | | 2(2x-21)=360-2(x) | | 2x-3(2+x)=4x+12 | | .6+.33m=.4 | | X/4=8/3? | | 7x+10=5(x-2) | | 15x+159= | | 1.1+inx^2=6 | | 15x^2+102x-72=0 | | F(X)=2x^3-5x^2-x+14F(4) | | 5x-15=30+2x | | 7x-4(2x-9)=50 | | (1/2x)-4=3-(1/3x) | | 23-2x=22 | | 9f+6g-4f-2g+2= |

Equations solver categories